Performance of syndromic management for the detection and treatment of genital Chlamydia trachomatis, Neisseria gonorrhoeae and Trichomonas vaginalis among women attending antenatal, well woman and sexual health clinics in Papua New Guinea: a cross-sectional study. Issue 12 (29th December 2017) - Vallely, Lisa M; Toliman, Pamela; Ryan, Claire; Rai, Glennis; Wapling, Johanna; Gabuzzi, Josephine; Allen, Joyce; Opa, Christine; Munnull, Gloria; Kaima, Petronia; Kombuk, Benny; Kumbia, Antonia; et al.
Abstract : Objective: Papua New Guinea (PNG) has among the highest estimated prevalences of genital Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) and Trichomonas vaginalis (TV) of any country in the Asia-Pacific region. Diagnosis and treatment of these infections have relied on the WHO-endorsed syndromic management strategy that uses clinical presentation without laboratory confirmation to make treatment decisions. We evaluated the performance of this strategy in clinical settings in PNG. Design: Women attending antenatal (ANC), well woman (WWC) and sexual health (SHC) clinics in four provinces were invited to participate, completed a face-to-face interview and clinical examination, and provided genital specimens for laboratory testing. We estimated the performance characteristics of syndromic diagnoses against combined laboratory diagnoses. Results: 1764 women were enrolled (ANC=765; WWC=614; SHC=385). The prevalences of CT, NG and TV were highest among women attending ANC and SHC. Among antenatal women, syndromic diagnosis of sexually transmitted infection had low sensitivity (9%–21%) and positive predictive value (PPV) (7%–37%), but high specificity (76%–89%) and moderate negative predictive value (NPV) (55%–86%) for the combined endpoint of laboratory-confirmed CT, NG or TV. Among women attending WWC and SHC, 'vaginal discharge syndrome' had moderate to high sensitivity (72%–78%) and NPV (62%–94%), but low specificity (26%–33%) and PPV (8%–38%). 'Lower abdominal pain syndrome' had low sensitivity (26%–41%) and PPV (8%–23%) but moderate specificity (66%–68%) and high NPV (74%–93%) among women attending WWC, and moderate-high sensitivity (67%–79%) and NPV (62%–86%) but low specificity (26%–28%) and PPV (14%–33%) among SHC attendees. Conclusion: The performance of syndromic management for the detection and treatment of genital chlamydia, gonorrhoea and trichomonas was poor among women in different clinical settings in PNG. New diagnostic strategies are needed to control these infections and to prevent their adverse health outcomes in PNG and other high-burden countries.